Low Field Magnetic Stimulation Ameliorates Schizophrenia-Like Behavior and Up-Regulates Neuregulin-1 Expression in a Mouse Model of Cuprizone-Induced Demyelination - Sun, Zuoli; Jiang, Tianhe; Wu, Yan; Ma, Chao; He, Yi; Yang, Jian (Frontiers in Psychiatry, 2018)
White matter and myelin sheath integrity are disrupted in schizophrenia, and non-invasive magnetic brain stimulation targeting these tracts is a promising new therapeutic approach. In particular, deep-brain reachable low field magnetic stimulation (DMS) could alleviate cognitive impairment and depressive-like behaviors in animal models. In this study, we sought to assess the effects of DMS on myelin sheath damage and schizophrenia-like behaviors in the cuprizone-induced demyelination mouse model. Mice were fed cuprizone (copper ion chelating agent, 0.2% w/w mixed with food) for 6 weeks to induce demyelination. During these 6 weeks, mice were stimulated with either sham, low-frequency (LFS, delta frequency) DMS or high-frequency (HFS, gamma Hz) DMS for 20 minutes each day. Behavioral tests were conducted 24 h after the final DMS session. The myelin sheath was examined by immunohistochemistry and the expression of NRG1/ErbB4 in the prefrontal cortex was measured with Western blotting. Six weeks of HFS significantly alleviated schizophrenia-like behaviors in cuprizone mice, including improved nesting, social interaction and sensorimotor gating, while LFS improved sensorimotor gating only. HFS and LFS both repaired the myelin sheath and increased the expression of neuregulin-1 and its receptor ErbB4, in the prefrontal cortex of demyelinated mice. Our findings show that DMS is a potential effective neuromodulation technique for the treatment of schizophrenia. One possible mechanism underlying these therapeutic effects could involve the up-regulation of neuregulin-1/ErbB4 signaling in the prefrontal cortex.